Risk management in the sphere of state economic security provision using professional liability insurance - O. Faiier; O. Arefieva; I. Miahkykh; N. Babko; S. Kuskova; O. Khloponina-Gnatenko (Global Journal of Environmental Science and Management)
This study contains a comprehensive scientific analysis of modern problems of risk management in the sphere of state economic security provision using professional liability insurance. The elements of the mechanism for providing economic security are defined, namely: subjects, objects, and instruments of influence. It is stipulated that insurance is the means to provide state economic security. Here are types of insurance that are important for the state and its economic security and we have focused on one of these types, namely: professional liability insurance. It is shown that this type of insurance helps to manage the risks in different business activities. The concept of this type of insurance has been researched. It is identified as its characteristics. The classification of this type of insurance has been performed. It is proved the effectiveness of insurance as a method to provide the protection of the economic interests of all entities by transferring part of the risks to professional participants of the insurance market.